Psychotherapy can be effective in prolonging periods free of depression in early senescent - Bhagat, Vidya (Bangladesh Journal of Medical Science, 2016)
Background: The Psychotherapy can be effective in prolonging periods free of depression in early senescent has been focused on the study. People refused medication agreed to come for psychotherapy are treated to get free from their depressive symptom. The main objective of the study was therefore using psychotherapy as a treatment module to stretch time free of depression. Further psycho education to give more information on depression and increase patient flexibility for the combination of anti-depressant with psychotherapy when needed. Methodology: The subjects selected for the study were 60 patients from Nitte Rural Psychiatry Clinic Nitte Mangalore Karnataka, India. They were selected by random sampling technique. Medico-Psychological questionnaire for general neuroticism was administered to find out the extent of depression before and after psychotherapy. To find the difference between the age and depression before and after psychotherapy Carl Pearsons Correlation coefficient method was carried out. Results: The results reveal that a non-significant difference between age groups with extent of depression in different age group of early senescent before and after psychotherapy (Chi-square=1.7913, p>0.05) at the 5 % level of significance and (Chi-square=2.4485, p>0.05) at the 5 % level of significance respectively. Further the Comparison of extent of depression before and after psychotherapy in 50-55, 56-60 age groups and as a total by Wilcoxon matched pairs test has been administered and the result reveals that significant differences between extent of depression before and after psychotherapy in 50-55yrs of age group (Z=2.5205, p<0.05) at the 5 % level of significance, 56-60yrs of age group (Z=2.2014, p<0.05) at the 5 % level of significance. It means that, the significant means that, the significance of 15.7%, 10.5%depression was decreased before and after psychotherapy respectively. A significant difference was observed between extent of depression before and after psychotherapy in 50-60yrs of age group (Z=3. 2958, p<0.05) at the 5 % level of significance. It means that, the significance of 13.0% depression was decreased after psychotherapy. Conclusion: The implication of this study was to develop insight and understanding among the clinicians that importance psychotherapy as treatment of depression. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.118-122